Hubungan Pengetahuan Ibu Tentang Gizi Balita dengan Status Gizi Balita di Desa Padaan Wilayah Kerja Puskesmas Pabelan Kabupaten Semarang: The Relationship Between Mothers' Knowledge About Toddler Nutrition and the Nutritional Status of Toddlers in Padaan Village, Pabelan Community Health Center Working Area, Semarang Regency - Samsi Rohmini; Risma Aliviani Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Nutritional status is a condition caused by a balance between the intake of nutrients from food with the needs of nutrients needed for the body's metabolism. One of the factors that affect toddler nutrition is maternal knowledge. The results of interviews conducted on 10 mothers who had toddlers in Cikalan obtained results from 4 out of 10 mothers lacking knowledge, 3 good knowledge and 3 sufficient knowledge. The issue of maternal knowledge is very important in determining food intake because a person's level of nutritional knowledge affects behavior in choosing foods that have an impact on the nutritional intake of their children. This study aims to determine the relationship between maternal knowledge about toddler nutrition with the nutritional status of toddlers in the village of padaan. The study used analytical methods with a cross sectional approach. The population of mothers who have toddlers aged 12-60 months in padaan village is 212 and the sample in this study is 68 mothers who have toddlers and 68 toddlers aged 12-60 months in padaan village. The sampling technique uses proportionate random sampling. The data collection tool used a questionnaire on maternal knowledge about toddler nutrition, while for nutritional status assessment using the Z-Score (BB/U) table. The statistical test was analyzed by chi-square test with a significant level (α) = 0.05. The results of the study obtained a picture of maternal knowledge about toddler nutrition in the village of padaan from a total of 68 respondents, most of whom had less knowledge as many as 46 mothers (67.6%), a picture of nutritional status in toddlers in the village in the category of nutritional status was lacking with a total of 36 toddlers (53%). The chi-square test showed a value of ρ = 0.169 α value = 0.05, there was no relationship between maternal knowledge of toddler nutrition and nutritional status. It is expected that mothers pay more attention to the importance of nutrition for toddlers, and seek information about meeting nutritional needs such as attending counseling and counseling from puskesmas and other mass media. ABSTRAK Status gizi adalah keadaan yang diakibatkan oleh keseimbangan antara asupan zat gizi dari makanan dengan kebutuhan zat gizi yang diperlukan untuk metabolisme tubuh. Faktor yang mempengaruhi gizi balita salah satunya adalah pengetahuan ibu. Hasil wawancara yang dilakukan pada 10 ibu yang memiliki balita di cikalan didapatkan hasil 4 dari 10 ibu pengetahuan kurang, 3 pengetahuan baik dan 3 pengetahuan cukup. Masalah pengetahuan ibu sangat penting peranannya dalam menentukan asupan makanan karena tingkat pengetahuan gizi seseorang berpengaruh terhadap perilaku dalam memilih makanan yang berdampak pada asupan gizi anaknya. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan ibu tentang gizi balita dengan status gizi balita di desa padaan. Penelitian menggunakan metode analitik dengan pendekatan cross sectional. Populasi ibu yang mempunyai balita usia 12-60 bulan di desa padaan yaitu 212 dan sampel dalam penelitian ini adalah 68 ibu yang mempunyai balita dan 68 balita usia 12-60 bulan di desa padaan. Teknik sampling menggunakan proportionate random sampling. Alat pengumpulan data menggunakan kuesioner pengetahuan ibu tentang gizi balita, sedangkan untuk penilaian status gizi menggunakan tabel Z-Score (BB/U). Uji statistic dianalisis dengan uji chi-square dengan taraf signifikan (α) = 0,05. Hasil penelitian didapatkan gambaran pengetahuan ibu tentang gizi balita di desa padaan dari total 68 responden sebagian besar mempunyai pengetahuan kurang sebanyak 46 ibu (67,6%), gambaran status gizi pada balita di desa padaan kategori status gizi kurang dengan jumlah 36 balita (53%). Uji chi-square menunjukkan nilai ρ = 0,169 nilai α = 0,05, tidak ada hubungan antara pengetahuan ibu tentang gizi balita dengan status gizi. Diharapkan kepada ibu lebih memperhatikan kan pentingnya gizi untuk balita, dan mencari informasi tentang pemenuhan kebutuhan gizi seperti mengikuti penyuluhan dan konseling dari puskesmas serta media massa lainnya.